Researching the hard-to-reach: a scoping review protocol of digital health research in hidden, marginal and excluded populations - Belt, RV; Rahimi, K; Cai, S (BMJ Publishing Group, 2022)
Introduction There is a significant growth in the use of digital technology and methods in health-related research, further driven by the COVID-19 pandemic. This has offered a potential to apply digital health research in hidden, marginalised and excluded populations who are traditionally not easily reached due to economic, societal and legal barriers. To better inform future digital health studies of these vulnerable populations, we proposed a scoping review to comprehensively map published evidence and guidelines on the applications and challenges of digital health research methods to hard-to-reach communities.